2013
DOI: 10.1073/pnas.1311784110
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5 dimethylates R30 of the p65 subunit to activate NF-κB

Abstract: The ubiquitous inducible transcription factor NF-κB plays central roles in immune and inflammatory responses and in tumorigenesis. Complex posttranslational modifications of the p65 subunit (RelA) are a major aspect of the extremely flexible regulation of NF-κB activity. Although phosphorylation, acetylation, ubiquitination, and lysine methylation of NF-κB have been well described, arginine methylation has not yet been found. We now report that, in response to IL-1β, the p65 subunit of NF-κB is dimethylated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
225
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(239 citation statements)
references
References 38 publications
(43 reference statements)
14
225
0
Order By: Relevance
“…The similar phenomenon, which is that the expanded myeloid cells and T cells are induced in reaction to autoimmunity and inflammation, was found in mice lacking genes involved in NF-kB activation (45)(46)(47). Previously, NF-kB was also reported to be regulated by other PRMTs (48)(49)(50), suggesting that arginine methylation plays unique roles in NF-kB activation. In addition, it has been reported that histone arginine deimination, which antagonizes arginine methylation, is a response to a wide range of inflammatory stimuli (51,52).…”
Section: Discussionsupporting
confidence: 58%
“…The similar phenomenon, which is that the expanded myeloid cells and T cells are induced in reaction to autoimmunity and inflammation, was found in mice lacking genes involved in NF-kB activation (45)(46)(47). Previously, NF-kB was also reported to be regulated by other PRMTs (48)(49)(50), suggesting that arginine methylation plays unique roles in NF-kB activation. In addition, it has been reported that histone arginine deimination, which antagonizes arginine methylation, is a response to a wide range of inflammatory stimuli (51,52).…”
Section: Discussionsupporting
confidence: 58%
“…We demonstrate that PRMT1 forms a cellular complex with RelA and asymmetrically dimethylates the conserved R30 residue in the RelA DNA-binding L1 loop. The asymmetric dimethylation of RelA by PRMT1 is enhanced after prolonged treatment of cells with TNFα and, in contrast to the symmetric modification (16,17), negatively regulates the DNA binding and transcriptional activity of RelA. We also find that down-regulation of PRMT1 enhances the expression of NF-κB target genes after TNFα stimulation by facilitating RelA recruitment to specific promoters.…”
Section: Significancementioning
confidence: 54%
“…The RelA L1 loop, which is critical for nucleotide sequence recognition and binding, has been shown to be monomethylated at K37 by SET7/9 (12) and symmetrically dimethylated at R30 by PRMT5 (16). These modifications cause an increase in the RelA affinity to DNA and activate NF-κB, in contrast with the inhibitory asymmetric R30 dimethylation by PRMT1 identified in our study.…”
Section: (7)mentioning
(Expert classified)
See 1 more Smart Citation
“…Increased activity of the PRMT5-MEP50 complex is found in many kinds of cancer cells and highly correlated with poor prognosis of human cancers, and it is the potential target for treatment of cancers (19). PRMT5 participates in inflammatory response by methylation modification of R35 or R30 of p65 to regulate interleukin-1α (IL-1α), TNF receptor-associated factor 1 (TRAF1), or CXCL10 expression (29). H3R8me2s and H4R3me2s repress gene expression, although the mechanisms mediated with PRMT5 remain to be elucidated (30).…”
Section: Ca-vi B Associates With Prmt5 To Promote C-rel Recruitment Tmentioning
confidence: 99%